Companion to contemporary political philosophy / edited by Robert E. Goodin and Philip Pettit - "Goodin, Robert E. (ed.)" (Oxford, 2000)
A comprehensive guide to current thinking in political philosophy, this volume focuses especially on normative issues. The first part of the book consists of a series of extended essays on the contribution that a number of different disciplines - economics, history, legal studies, political science, sociology, and philosophy itself - have made and are making to current debates. Analyses of political ideologies form a separate section, followed by discussions of major concepts ranging from virtue and equality to sociobiology and environmentalism. Written by an international assembly of today's most distinguished figures in political philosophy, this volume provides an ideal text for course use.
Keywords: Philosophy-History